Restorative Justice as an Alternative in the Indonesian Criminal Justice System - Valentino, Cecilia Rudolf (Journal of Progressive Law and Legal Studies, 2025)
This study examines in depth the application and potential of restorative justice as an alternative approach in the criminal justice system in Indonesia. Unlike the traditional retributive model, which emphasizes punishment, restorative justice emphasizes relationship restoration, reconciliation, and active community involvement in addressing criminal behavior. The Indonesian legal system, which is based on a combination of civil and customary law traditions, creates a conducive foundation for the application of restorative justice principles. This study examines relevant legal provisions, including Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and diversion mechanisms, in addition to traditional conflict resolution practices deeply rooted in Indonesian society. The study's key findings indicate that restorative justice has significant potential to reduce recidivism rates, reduce overcrowding in correctional institutions, and restore social harmony while still accommodating the needs of victims. However, its implementation still faces several challenges, such as limited institutional capacity, lack of adequate training for law enforcement officers, and uneven implementation across regions. Based on the analysis, this study concludes that effective integration of restorative justice requires comprehensive legal reform, closer coordination among stakeholders, and cultural sensitivity to Indonesia's social diversity. These efforts are believed to foster a more humane, responsive, and sustainable criminal justice system, one that balances victim protection, offender development, and the interests of society as a whole.